Neoadjuvant Immunotherapy in Head and Neck Cancers: A Paradigm Shift in Treatment Approach - Alessia Zotta; Maria Luisa Marciano; Francesco Sabbatino; Alessandro Ottaiano; Marco Cascella; Monica Pontone; Massimo Montano; Ester Calogero; Francesco Longo; Morena Fasano; Teresa Troiani; Fortunato Ciardiello; et al. (Biomedicines)
Checkpoint inhibitors (ICIs) have demonstrated substantial efficacy in the treatment of numerous solid tumors, including head and neck cancer. Their inclusion in the therapeutic paradigm in metastatic lines of treatment has certainly improved the outcomes of these patients. Starting from this assumption, numerous studies have been conducted on ICIs in other earlier disease settings, including studies conducted in patients in neoadjuvant settings. However, how many and which studies are truly significant? Can they lay concrete foundations for further future studies and therefore allow us to continue to have this interesting future perspective? Through a review of the existing literature, coupled with insights gleaned from clinical practice and from the main recently published studies, we aim to examine the therapeutic potential of ICIs in patients affected by head and neck cancer in a neoadjuvant treatment setting and encourage researchers to set up successful future clinical trials.